Graphite Application and Different Powers of Neodymium-Doped Yttrium Aluminium Garnet (Nd:YAG) Laser on Dentin Surface Changes: A Scanning Electron Microscopy Study - Birang, Reza; Yaghini, Jaber; Fakhari, Elham; Hasheminia, Seyed Mohsen; Mousavi, Maryam; Farhadzadeh, Mahnaz; Birang, Ehsan (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Various methods have been used for the treatment of dentine hypersensitivity such as dentifrices, sealants and different types of lasers. The aim of this study was to evaluate the effect of Neodimium:Yttrium-Aluminium-Garnet (Nd:YAG) laser in association with graphite on the dentin morphologic changes. METHODS: In this experimental in vitro study, 16 freshly extracted third molars were selected. 5 specimens with the dimensions of 2×2×1 mm from root trunk were prepared. Specimens were randomly divided into five groups: group 1 (control, no laser irradiation). Group 2, 3 irradiated by Nd:YAG laser 0.5 and 1W, output power respectively. Group 4, 5 smeared with graphite and then irradiated by Nd: YAG laser 0.5 and 1W output power. Samples were prepared for scanning electron microscopy. Number and diameter of dentinal tubules were determined in different groups and analyzed with the Kruskal-wallis and Mann-Whitney tests (SPSS 16). RESULTS: The number of tubules had significant difference between all groups (P<0.001), except group 1 in comparison with group 2 (P> 0.05), and group 3 in comparison with group 4 (P> 0.05). Micro-cracks and rupture of melted dentin materials were seen in group 4 and 5. CONCLUSION: According to the findings of this study, smearing with graphite on dentin surface increase the absorption of Nd:YAG laser energy and reduced the diameter and number of open dentinal tubules.